The Effect of Service Quality and Customer Satisfaction on Customer Trust and Loyalty at PT. Bank Rakyat Indonesia (Persero) Tbk in Pekanbaru Branch Office, Tuanku Tambusai - Dian Sukma Rini; Susi Hendriani; Gatot Wijayanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
This study aims to examine customer loyalty and satisfaction at PT Bank Rakyat Indonesia (BRI), Tuanku Tambusai Branch Pekanbaru, focusing on the impact of service quality and customer satisfaction on trust and loyalty. Using quantitative methods with a survey of BRI customers, this study analyzed responses through statistical tests to validate hypotheses. Sampling included active customers, assessing service quality, trust, and loyalty variables. Data was collected through a structured questionnaire, measuring variables on a Likert scale. Analysis revealed that service quality and satisfaction significantly affect customer trust and loyalty, supporting the hypothesis that trust is a mediator in the relationship between service quality and loyalty. The findings highlight the requirement for BRI to improve service quality to build stronger customer trust and loyalty, emphasizing the role of service standards in customer retention.